Clinical study on the unloading effect of hip bracing on gait in patients with hip osteoarthritis. (April 2017) - Nérot, Agathe; Nicholls, Micah
Background: Internal hip abduction moment is a major indicator for hip loading. A new hip bracing concept was designed to unload the cartilaginous area in hip osteoarthritis via an abduction and external rotation force intended to alter the weight bearing area and reduce compression through the joint. Objective: To assess the effect of a novel brace on hip rotation in the transverse and coronal planes and on the hip abduction moment. Study design: Repeated measures. Methods: Gait analysis was performed on 14 subjects with unilateral symptomatic hip osteoarthritis. Pain, joint motion, moments and vertical ground reaction force were compared between the braced and the unbraced (control), randomly assigned, conditions. Results: Nine participants felt an immediate reduction in pain while walking with the hip brace. Peak hip abduction moment significantly decreased on the osteoarthritis side ( p = 0.017). Peak hip adduction ( p = 0.004) and internal rotation ( p = 0.0007) angles significantly decreased at stance with the brace. Conclusion: Wearing the brace would appear to reduce the compressive joint reaction force at the femuroacetabular interface as indicated by a reduction in internal hip abduction moment along with immediate pain reduction in nine participants. Further long-term studies are warranted. Clinical relevance: The brace rotates the hip in the transverse and coronal planes, possibly resulting in a decrease in load through the diseased area of cartilage. In some patients, an immediate decrease in pain was experienced. The brace offers an alternative solution for hip osteoarthritis patients not ready for a hip replacement.